The role of colleges of education in achieving sustainable development goals: An overview of Saudi’s Vision 2030 from an educational perspective - Al-Subaie, Faisal Shabib Muslat; Saini, Shivani; Darras, Ghada Mohammed Hassan (Research Journal in Advanced Humanities, 2024)
The current study is based on the idea of achieving SDG 4 (Sustainable Development Goal 4) and its indicators. The Vision of the Kingdom of Saudi Arabia 2030 AD encompasses the Arab and Islamic depth through a vibrant society, a prosperous economy, and an ambitious nation, which emphasized the concepts of sustainable development as its goals in several sections, such as ensuring environmental sustainability, reducing pollution of all kinds, enabling a healthy life, and enhancing identity. Nationalism, the values of justice and transparency, improving equal access to education, developing the digital economy, and other goals were consistent with the concepts of sustainable development, and in response to global trends and recommendations of previous conferences and studies, and given the pivotal role of colleges of education, the current study aimed to reveal the role of colleges of education in Achieving sustainable development goals from an educational perspective (Prince Sattam bin Abdulaziz University as a model), where the study relied on the descriptive analytical approach, data was collected through a questionnaire consisting of (36) statements, divided into three dimensions (the social dimension - the economic dimension - the environmental dimension), it was distributed to a sample of students (501) from the College of Education. The research used SDG 4 (Sustainable Development Goal 4) and it’s indicators to ensure that all the SDG 4 goals achieved in due proportion. The results of the study revealed to achieving SDG 4 (Sustainable Development Goal 4) and its indicators from an educational perspective to a high degree in all their social, economic, and environmental dimensions. It is expected that the results of the study will contribute to developing the programs of colleges of education to achieve the goals of sustainable development from an educational perspective. The study developed a set of recommendations for faculty members and those in charge of the educational process at the university to prepare a generation of teacher graduates capable of competing at all levels, drawing their energy from the cultural and Islamic depth of the Kingdom.